1978
DOI: 10.2307/1954105
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Campaign Spending in Congressional Elections

Abstract: Incomplete understanding of the connection between campaign spending and election outcomes has hindered evaluation of enacted and proposed congressional campaign finance reforms. Reanalysis of the 1972 and 1974 House and Senate campaign spending data using both OLS and 2SLS regression models shows that spending by challengers has a much greater impact on the outcome than does spending by incumbents. A similar analysis of the effects of spending on voters' recall of candidates in the 1972 and 1974 SRC surveys s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
395
4
40

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 536 publications
(460 citation statements)
references
References 15 publications
21
395
4
40
Order By: Relevance
“…Jacobson (1978), for example, suggests that challengers would be mostly hurt by contribution limits because his estimates suggest that the productivity of challenger spending is significantly larger than the productivity of incumbent spending. In contrast, Green and Krasno's (1988) finding that incumbents' and challengers' campaign spending has an equal marginal impact on their respective vote shares, suggests that contribution limits have an equal impact on incumbents and challengers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Jacobson (1978), for example, suggests that challengers would be mostly hurt by contribution limits because his estimates suggest that the productivity of challenger spending is significantly larger than the productivity of incumbent spending. In contrast, Green and Krasno's (1988) finding that incumbents' and challengers' campaign spending has an equal marginal impact on their respective vote shares, suggests that contribution limits have an equal impact on incumbents and challengers.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Some advocates favor limiting contributions because if limits were increased, "higher limits would increase the disparity in challenger-incumbent fundraising." 1 The academic debate regarding campaign spending's effect on vote shares goes back to Jacobson's (1978) groundbreaking study on the issue. Since his initial work, many scholars have analyzed this relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of the relation between money and electoral success has stirred the interest of political scientists ever since systematic data on campaign finance have become available. Researchers have analyzed the relation between money and votes, having identified specific patterns, as in the work by Jacobson (1978) on how political finance affects incumbents and challengers differently and that by Coate (2004) on the informational value of electoral expenditures 1 . On the other hand, the literature also points to multidirectional causal relations, since money may yield votes, yet the expectation of future voting may drive donations, while both-donations and votes -may result from characteristics of candidates and donors (STRATMAN, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Those who have joined politics are bound to stay in politics. In this article our interest in the candidates' track record builds on the assumption that electoral capital can mediate the relation between money and electoral success (JACOBSON, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that candidates can receive a vote for approximately every $10 they spend (53,54). This creates a system of ''one dollar, one vote,'' which is the definition of a plutocracy, not a democracy.…”
Section: Our Institutions Are Designed To Maximize Energy and Resourcmentioning
confidence: 99%